Het Locatiefsubstitutief in het Cilubà - Horvath, Ellen; Kabuta, Ngo Semzara (Afrika Focus, 1998)
In this article we will examine the correlation between tonology and syntax in connection with the locative substitutives (LS), or locative independent pronouns in Cilubà, spoken in both Kàsaayi provinces of Congo. We will show that the tonology of the LS depends on its syntactic position in the sentence. In contrast to the substitutives of classes 1 through 8 and 11 through 15 and of the participants, which generally have a fixed tone pattern, namelyfalling-high, theLS (classes 16 through 18) display three possible tone patterns, depending on their position in the sentence. These tone patterns are: falling-high, rising-low, high-low. KEY WORDS: Cilubà, locative substitutive, syntax, tonology